The Influence of Leadership Style and Work Motivation on Employee Job Satisfaction at CV Deli Motor - Jenni Sahputri; Rifky Budi Setiawan (Penerbit Jurnal Indonesia, 2025)
Job satisfaction is a positive feeling or attitude that a person has towards their job. Job satisfaction not only impacts individual employees but also improves overall organisational performance. This study examines the relationship between leadership style, work motivation, and employee job satisfaction at CV Deli Motor. With increasing competition in the automotive industry, companies need to pay attention to factors that affect employee job satisfaction to increase productivity and loyalty. This study uses a quantitative approach with a survey method of 36 employees of CV Deli Motor. Data were collected through questionnaires and analysed using multiple regression analysis. The results showed that partially leadership style does not have a positive and significant effect on employee job satisfaction, while work motivation variables have a positive and significant effect on employee job satisfaction. Based on the results of the F test, the variables of leadership style and work motivation simultaneously have a positive and significant effect on employee job satisfaction. The coefficient of determination shows that the magnitude of the influence of leadership style and work motivation on employee job satisfaction is 34.1% and the rest is influenced by other variables not examined in this study.